Estrategias de auto-estudio para mejorar la comprensión de textos escritos en inglés en estudiantes de tercer grado de secundaria en la institución educativa Sagrado Corazón De Iquitos 2023 - Ruiz Najar, Julia Nicole (2025)
This research evaluated the positive effects of implementing an educational program focused on self-study strategies in all-girls school. The purpose was to enhance English reading comprehension in third grade secondary school students at the Sagrado Corazon Educational Institution, Iquitos 2023. The research is evaluative, with designs field study, contemporary transectional, univariable, and quasi experimental. The non-probabilistic sample consisted of 59 students: one experimental (30) and one control (29). For the data collection, a valid and reliable written comprehension test was used. It was identified that experimental group students demonstrated significant improvement in three of the four capabilities analyzed in comparison to the control group. The analysis with differences on 0-20 scale were: reading comprehension in English (11,68 > 9,62), Gets information (14,19 > 9,63), Infers and interprets (11,33 > 8,27). However, in Evaluates the form, content and context, the result was lower (7,84 < 11,11). To conclude, the implemented educational program significantly improved the English reading comprehension among third grade students at Sagrado Corazon high school.